TEM investigations on the local microstructure of electrodeposited galfenol nanowires. (9th December 2015) - Pohl, D; Damm, C; Pohl, D; Schultz, L; Schlörb, H
Abstract: The local microstructure of Fe–Ga nanowires is investigated considering dependence on the deposition technique. Using a complexed electrolyte, smooth and homogeneous Fe80 Ga20 nanowires are deposited into anodic aluminum oxide templates by either applying pulse potential or potentiostatic deposition technique. At optimized deposition conditions the wires show the desired composition of Fe80±2 Ga20±2 without a gradient along the growth direction. Composition distribution, structure and microstructure are examined in detail and reveal only minor differences. Line EELS and crystal lattice measurements reveal a negligible oxygen content for both preparation routines. Neither Fe/Ga oxides nor hydroxides were found. Both potentiostatically deposited as well as pulse deposited nanowires exhibit a preferred 〈110〉 orientation, the latter with slightly larger crystals. Different contrast patterns were found by TEM that appear more pronounced in the case of pulse deposited wires. High resolution transmission electron microscopy analysis and comparison of differently prepared focused ion beam lamellas reveal that these contrasts are caused by defects in the alternating potential deposition itself and are not induced during the TEM preparation process. The alternating potential mode causes periodic growth thereby inducing different layers with reduced wire thickness/defects at the layer interfaces.